2021
DOI: 10.1021/acs.jmedchem.1c00226
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Repressive Complex 2 Modulation through the Development of EZH2–EED Interaction Inhibitors and EED Binders

Abstract: Epigenetics is nowadays a well-accepted area of research. In the last years, tremendous progress was made regarding molecules targeting EZH2, directly or indirectly. Recently tazemetostat hit the market after FDA-approval for the treatment of lymphoma. However, the impairment of EZH2 activity by orthosteric intervention has proven to be effective only in a limited subset of cancers. Considering the multiproteic nature of the PRC2 complex and the marked dependence of EZH2 functions on the other core subunits su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…28 Building on these findings, two recent studies reported EED-directed bifunctional degraders using EED226-derived moieties linked to a well-established von Hippel−Lindau (VHL) ligand to induce rapid proteasomal degradation of not only EED but also EZH2 and SUZ12, which in turn led to selective proliferation inhibition of PRC2dependent cancer cells. 29,30 Moreover, further optimized EED ligands with high potency and efficacy in tumor models in mice were reported by multiple groups since the first disclosures of EED binders in 2017 (reviewed recently by Tomassi et al 31 ). 32−35 Although EED226 displayed an overall favorable profile regarding selectivity, bioavailability, and efficacy in an EZH2 mut xenograft model, further advancement of this compound was limited by its moderate solubility and permeability as well as the existence of the monosubstituted electron-rich furan ring, which is prone to ring oxidation and reactive metabolite formation.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…28 Building on these findings, two recent studies reported EED-directed bifunctional degraders using EED226-derived moieties linked to a well-established von Hippel−Lindau (VHL) ligand to induce rapid proteasomal degradation of not only EED but also EZH2 and SUZ12, which in turn led to selective proliferation inhibition of PRC2dependent cancer cells. 29,30 Moreover, further optimized EED ligands with high potency and efficacy in tumor models in mice were reported by multiple groups since the first disclosures of EED binders in 2017 (reviewed recently by Tomassi et al 31 ). 32−35 Although EED226 displayed an overall favorable profile regarding selectivity, bioavailability, and efficacy in an EZH2 mut xenograft model, further advancement of this compound was limited by its moderate solubility and permeability as well as the existence of the monosubstituted electron-rich furan ring, which is prone to ring oxidation and reactive metabolite formation.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Importantly, EED226 displayed an inhibitory effect on the methyltransferase activity of both EZH1- and EZH2-harboring PRC2 and antiproliferative activity in cell lines with acquired EZH2 mutations, including those exhibiting resistance to SAM-competitive EZH2 inhibitors . Building on these findings, two recent studies reported EED-directed bifunctional degraders using EED226-derived moieties linked to a well-established von Hippel–Lindau (VHL) ligand to induce rapid proteasomal degradation of not only EED but also EZH2 and SUZ12, which in turn led to selective proliferation inhibition of PRC2-dependent cancer cells. , Moreover, further optimized EED ligands with high potency and efficacy in tumor models in mice were reported by multiple groups since the first disclosures of EED binders in 2017 (reviewed recently by Tomassi et al). …”
Section: Introductionmentioning
confidence: 99%
“…The scaffolding functions of EZH2, acting independently of its methyltransferase activity, may contribute to the more potent effects of EZH2 protein suppression 64,65 . Inhibitors that disrupt PRC2 complex stability, for instance by targeting the core subunit EED 66,67 , or EZH2 degraders 6870 , may offer more potent PRC2 complex and EZH2 suppression. Alternatively, systemic inhibition of EZH2 using small molecule inhibitors undoubtedly impacts non-tumor cells as well, and their deleterious effects on T cell function and proliferation could reduce their anti-tumor activity 71 .…”
Section: Discussionmentioning
confidence: 99%
“…In the PRC2 complex, EED has a regulatory role involving sensing the methylation status of H3K27me3-tagged histones, thus enabling positive allosteric control of EZH2 catalysis [37]. Specifically, engagement of the aromatic cage and top surface of EED by H3K27me3 stimulates the folding of an unstructured region of EZH2 into an alpha helix.…”
Section: Binding Mode Of Compound 1 Targeting Eed-ezh2mentioning
confidence: 99%